Curso Técnico em Eletromecânica do Colégio Técnico Industrial de Santa Maria (CTISM) e as expectativas do mundo do trabalho - Militz, Cássia de Fátima de Souza (2019)
This paper aims to show a parallel concerning the structure of the Subsequent Electromechanical Course, offered by CTISM - Industrial Technical College of Santa Maria and as requirements and demands currently existing in the main groups of companies hired by the workforce exercised by the last course in Santa Maria city. After all, new professionals or those who intend to develop in this work environment, receive the requirements demanded by the contractors and, consequently, meet the planning and offer requirements of Technological Education: Meeting the demands of the market, labor market and society; A reconciliation of the demands identified with a vocation of the educational institution and its real conditions of viability; The identification of individual professional profiles of each course, according to the demands and in line with the policies of promotion of the sustainable development of the country. Thinking about the concept of Vocational Education: a technological vocational education, integrated to different forms of education, work, science and technology, aims to guarantee the right to the right to acquire professional skills that are made suitable for insertion in the professional sectors in which the technologies are used to absorb this kind of workforce. This paper seeks to contribute not only to the contracting companies, but also to teachers involved in professional education, students who seek opportunities to enter the work world and often build them through professional education, and even more broadly to an entire society that invests directly and indirectly in quality public education, including the Industrial Technical College of Santa Maria, through an update of concepts and practices taught in the Electromechanical Technician Program, from the perspective of the industries that contract this workforce in Santa Maria, RS. The research methodology used in this paper was the semi-structured interview, with the use of questionnaires applied to the managers of the companies participating in the research.